THE EFFECT OF SCRIPTED SONGS TECHNIQUE ON STUDENTS’ ENGLISH COMPETENCE (An Experimental Study of Fourth Grade Students of SD Negeri No 6 Dalung, Kuta Utara Sub-District, Badung in Academic Year 2013/2014) - Wulandari T, P.; Ratminingsih, N. M.; Budasi, I G. (Jurnal Pendidikan Bahasa Inggris undiksha, 2018)
This experimental study aimed at finding out the significant effect of Scripted Songs technique and conventional teaching technique towards English competences of fourth grade students of SD Negeri No 6 Dalung, Kuta Utara Sub-District, Badung in academic year 2013/2014. The design of this study was post-test only control group design. The implementation of cluster random sampling technique showed that class 4.A as the control group which was taught by using conventional teaching technique and class 4.C as the experimental group which was taught by using Scripted Songs technique. Both groups consisted of 40 students each. The results of data analysis showed that the students who were taught by implementing Scripted Songs technique performed better than those who were taught by implementing conventional teaching technique. The mean score of experimental group was 79.1 and the control group was 75.5. The results of t-test analysis showed that the tobs was 3.755. It was higher than the value of the tcv at 1.99085 (α = 0.05). Moreover, the result of questionnaire indicated that the implementation of Scripted Songs technique motivated the students in comprehending English competences. In conclusion, Scripted Songs technique contributed in giving highly significant effect to students’ English competences. Keywords: Scripted songs, English competences